Selected Topics on Business Informatics: Editorial Introduction to Issue 20 of CSIMQ - Zdravkovic, Jelena (Complex Systems Informatics and Modeling Quarterly, 2019)
This issue complements the previous issue in the way that it aggregates some prominent research results of the 17th International Conference on Perspectives in Business Informatics Research (BIR2018) in Stockholm, Sweden, in September 24-26, 2018 together with a recent research in the Business Informatics discipline and thus makes this issue highly actual. The topics of the issue concern improvements of enterprise architecture modeling and management in the directions of automation, adaptivness, digitalization and security with privacy.